Occupational uranium exposure and cardiovascular mortality: cohort and nested case-control studies for a better risk assessment. (19th October 2011) - Garsi, Jerome-Philippe; Canu, Irina Guseva; Chablais, Laetitia; Samson, Eric; Caer-Lorho, Sylvaine; Acker, Alain; Niogret, Christine; Laurier, Dominique
Abstract : Objectives: The risk of cardiovascular mortality (CVM) among French uranium workers after protracted low-dose exposure to different uranium compounds, was investigated among 2897 workers (79892 person-years) employed at Pierrelatte uranium processing plant (1960–2006). Methods: Cumulative exposure to different uranium compounds, classified by isotopic composition and solubility-type, was assessed using a plant-specific job-exposure-matrix linked to individual job records. HRs and associated 95%-CIs (HR (95% CI)) were estimated using Cox regression models accounting for sex, calendar period, initial socioeconomic status and associated exposure. Case-control study was nested into the cohort to address the role of individual biological and lifestyle parameters. Results: At the end of follow-up, 111 cases of CVM were observed. The CVM risk was increased only among workers exposed to insoluble compounds of reprocessed (HR=2.07(0.99 to 4.99), n=9) and natural uranium (HR=1.73 (1.11 to 2.69), n=41), after adjustment for solvents and heat exposure. The nested case-control study including all the CVM cases and 397 referents (matched 1:3 by sex and 5-year age class) is still ongoing for database completion (achieved at 75%) and analyses. Anthropometric (height, weight), biomedical (blood and urine biochemical analyses, diagnostic X-ray exposure), anamnesis and treatment, as well as smoking and alcohol consumption data were computerised on the annual basis using individual workers' occupational medicine records. Conclusions: Our cohort study is the first suggesting an increasing risk of CVM related to insoluble uranium exposure and the importance of solubility. The nested case-control study will refine our exposure-response analysis and provide results adjusted for known CVM risk factors in order to draw an appropriate conclusion.